2013
DOI: 10.1111/jsm.12283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yoga on Sexual Function in Women with Metabolic Syndrome: A Randomized Controlled Trial

Abstract: Introduction Female sexual dysfunction is an important public health issue; it has a high global prevalence, but no effective and safe treatment options. The prevalence of sexual dysfunction is higher in women with metabolic syndrome than in the general population. Aim The aim of this study was to investigate the efficacy of yoga as a treatment for sexual dysfunction in women with metabolic syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…In addition, many previous studies have dichotomized groups into exercise vs no exercise or designed randomized clinical trials with a preset exercise regimen. 10,26 To our knowledge, this is the first study to examine such varied and wide-ranging exercise activity levels in women. In light of our findings, increasing cumulative exercise activity from baseline appears beneficial, particularly for those exercising 47.4 weekly MET-hours at the outset.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, many previous studies have dichotomized groups into exercise vs no exercise or designed randomized clinical trials with a preset exercise regimen. 10,26 To our knowledge, this is the first study to examine such varied and wide-ranging exercise activity levels in women. In light of our findings, increasing cumulative exercise activity from baseline appears beneficial, particularly for those exercising 47.4 weekly MET-hours at the outset.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 30 studies that were included, 15 originated from India (Bera and Rajapurkar, 1993;Harbans et al, 2011;Hegde et al, 2013;Kanojia et al, 2013;Mahajan et al, 1999;Manjunath and Telles, 2012;McDermott et al, 2014;Mooventhan and Khode, 2014;Ray et al, 2001;Shukla and Gehlot, 2014;Telles et al, 2014;Telles et al, 2013;Thiyagarajan et al, 2015;Khatri et al, 2007;Manchanda et al, 2013), 8 from the USA (Blumenthal et al, 1989;Cohen et al, 2008a;Elavsky and McAuley, 2007a;Kanaya et al, 2014;Stachenfeld et al, 1998;Tracy and Hart, 2013 3 from Korea Seo et al, 2012;Kim et al, 2013), 2 from Taiwan (Chen et al, 2008;Chen et al, 2010), and one each from Japan (Sakuma et al, 2012) and China . Ten of the trials explicitly investigated overweight or obese individuals (Cohen et al, 2008a;Harbans et al, 2011;Kanaya et al, 2014;Lee et al, 2012;Seo et al, 2012;Shukla and Gehlot, 2014;Telles et al, 2014;Khatri et al, 2007;Kim et al, 2013;Manchanda et al, 2013); and three trials were conducted on children/adolescents (Bera and Rajapurkar, 1993;Seo et al, 2012;…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
“…Ten of the trials explicitly investigated overweight or obese individuals (Cohen et al, 2008a;Harbans et al, 2011;Kanaya et al, 2014;Lee et al, 2012;Seo et al, 2012;Shukla and Gehlot, 2014;Telles et al, 2014;Khatri et al, 2007;Kim et al, 2013;Manchanda et al, 2013); and three trials were conducted on children/adolescents (Bera and Rajapurkar, 1993;Seo et al, 2012;Telles et al, 2013). The sample size ranged from 17 to 204 with a median of 60.…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inconsistent with this study's results, Kim et al reported the effectiveness of a 12-week yoga session on improving sexual arousal and lubrication in women with metabolic syndrome and observed no significant difference between the intervention and control groups in sexual function scores. 31 Aerobic exercise involves continuous and often rhythmic muscle motions, which increase circulation and metabolic need for oxygen intake and improve cardiovascular condition. 17 In fact, regular physical exercises improve the circulatory system by strengthening the heart muscles and increasing blood volume.…”
Section: Discussionmentioning
confidence: 99%